Digital Transformation as a Strategy to Improve Marketing Performance and Public Financial Literacy - Muhammad Arif Zikir Risky; Dewi Puspitaningsih; Ninis Umnastuti; Irea Arrahima; Lala Hucadinota Ainul Amri; Zainudin Bin Siran (Universitas AMIKOM Yogyakarta, 2025)
This community service program aims to improve marketing performance and financial literacy among the community through the use of digital technology. The method used is a participatory approach, encompassing outreach, training, and mentoring for business owners and the community. Activities focused on the use of digital marketing (social media, marketplaces, and AI-based tools) and financial management using simple digital applications. Results showed increased understanding of digital marketing strategies among participants, their ability to create more effective promotional content, and improved skills in digital financial recording and management. Furthermore, there was increased awareness of the importance of financial literacy in supporting business sustainability. This activity contributes to providing a practical model for implementing digital transformation for the community, particularly UMKM. The practical implication of this activity is increased business competitiveness through the use of digital technology. Limitations of this activity lie in the relatively short duration of the mentoring and the varying levels of technology adaptation among participants.